IDENTIFIKASI Fusarium PENYEBAB PENYAKIT LAYU PADA TANAMAN CABAI (Capsicum annuum L.) DAN ENGENDALIANNYA DENGAN MIKORIZA VESIKULA ARBUSKULA (MVA) - , Afifah Nur Shobah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Red pepper (Capsicum annuum L.) i s fruit vegetables which is consumed daily. Chili needed from year to year but crop yield has decreased. This is caused by Fusarium wilt disease. Disease control is commonly used a fungicide but it may lead harmful residues to the environment. One alternative controlling that could be done is by utilizing vesicular arbuscular mycorrhizal (VAM) fungi. The purpose of this study was to identify the types of Fusarium wilt disease that attack pepper, select the Fusarium which had the highest effectively against Fusarium wilt disease and determine the effect of VAM inoculum to growth and suppression of Fusarium wilt disease intensity in pepper. Method of this research included isolation and identification of F. oxysporum causing Fusarium wilt of pepper plant roots, based on macroscopic and microscopic characters, surface color, presence or absence of color pigment, hyphae, macroconidia, microconidia and false heads. Then F. oxysporum was tested in vitro and in vivo by inoculating VAM, inoculation of F. oxysporum was done 6 weeks after VAM inoculum. Observation of the growth parameters included the number of leaves, plant height, root length, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, root disease index and the percentage of infected VAM. The results showed that treatment of VAM significantly affect the growth parameters but did not affect the presence of F. oxysporum. Fusarium wilt disease attacked in pepper were F. oxysporum and F. solani. with the highest intensity was the F. oxysporum. VAM inoculum affected plant growth and didnât affect the intensity of wilt disease suppression.